KEBIJAKAN PEMERINTAH DALAM MENERAPKAN KEWENANGAN DESA TERHADAP PENYELENGGARAAN PEMERINTAHAN MENURUT UNDANG-UNDANG NO.6 TAHUN 2014 - Masnun, Masnun; sepiyah, sepiyah (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2024)
This study aims to critically assess government policies in implementing village authority in governance based on Law No. 6 of 2014 concerning Villages. This law grants greater authority to villages to manage and regulate the interests of local communities based on initiatives, original rights, and/or traditional rights that are recognized and respected within the governance system of the Unitary State of the Republic of Indonesia. This research conducts a literature review of various relevant sources to analyze how government policies have been implemented at the village level and the challenges faced in their implementation. The study also explores the role of village governments in governance and the obstacles that arise due to limited resources, capacity, and support from both central and regional governments. The findings indicate that although Law No. 6 of 2014 provides a clear legal framework for villages to manage their own affairs, the implementation of these policies still faces numerous challenges. These include the lack of understanding and capacity of village officials, as well as suboptimal support from regional and central governments. This research suggests the need for enhancing the capacity of village officials and providing more concrete support from both central and regional governments to ensure that village authority can be effectively and efficiently exercisedThis study aims to critically assess government policies in implementing village authority in governance based on Law No. 6 of 2014 concerning Villages. This law grants greater authority to villages to manage and regulate the interests of local communities based on initiatives, original rights, and/or traditional rights that are recognized and respected within the governance system of the Unitary State of the Republic of Indonesia. This research conducts a literature review of various relevant sources to analyze how government policies have been implemented at the village level and the challenges faced in their implementation. The study also explores the role of village governments in governance and the obstacles that arise due to limited resources, capacity, and support from both central and regional governments. The findings indicate that although Law No. 6 of 2014 provides a clear legal framework for villages to manage their own affairs, the implementation of these policies still faces numerous challenges. These include the lack of understanding and capacity of village officials, as well as suboptimal support from regional and central governments. This research suggests the need for enhancing the capacity of village officials and providing more concrete support from both central and regional governments to ensure that village authority can be effectively and efficiently exercised